Influence of estrogen on skeletal muscle damage, inflammation, and repair - Tiidus, P. M. (Exercise and Sport Sciences Reviews, 2003)
Estrogen may influence the disruption and diminish or delay leukocyte infiltration that occurs after muscle damage. This paper examines a mechanism by which estrogen may diminish the early postdamage migration of neutrophils into muscle and discusses the potential implications of these effects on muscle repair.